Effect of Ultraviolet Photooxidation A and C on the Quality of Natural Antioxidant Cooking Oil of Tapak Dara Leaves (Catharanthus roseus L.) - Al-Bari, Akhmad; Saputri, Romadhiyana Kisno; Pitaloka, Ria Indah Kusuma (Proceeding International Conference on Religion, Science and Education, 2022)
Cooking oil is one of the commodities in Indonesia with a total production of 49.7 million tons in 2021, the largest of which is produced from palm oil extraction. Most of the use of cooking oil is still dominated by household consumption, restaurants, and biodiesel fuel purposes. Cooking oil for the household sector is generally obtained from traditional markets. Sellers in traditional markets leave the oil in an open container, place it in a damp place and expose it to sunlight. This causes it to not be durable, spoil quickly, and smell rancid due to oxidization to form aldehydes. Actions to slow down oxidation include adding synthetic and natural antioxidants like Tapak Dara. Tapak Dara is a natural herbal plant that contains 90.27% higher antioxidants than bitter melon and brotowali plants. The active compounds contained in tapak Dara include alkaloids, flavonoids, and terpenoids that can behave as antioxidants so that they can be added to the oil. This research was observed the decrease in oil quality within the addition of tapak Dara leaves under ultraviolet A (365nm) and C (254nm) exposure. Photooxidation was carried out with time variations of 1, 6, and 12 hours. The oxidation resistance can be seen from the damage value of the oil by measuring into several tests, namely the water content, peroxide number, and free fatty acids. The measurement results of tapak Dara leaf after photooxidation showed that there was a linear increase in the formation of free fatty acids (%FFA) and peroxide number with the length of time of photooxidation. The decreased quality was greater in UV-C photooxidation compared to UV-A. However, the curve tends to be flatter than the results of UV-A photooxidation. The water content test showed the opposite activity, UV-C photooxidation tends not to have an impact on increasing water content compared to UV-C photooxidation results.